Heartless : a pretty little liars novel - Shepard, Sara, 1977- (Shepard, Sara, 1977- Pretty little liars., 2010)
Hanna, Aria, Emily, and Spencer have been telling some outrageous stories, but no one seems to believe them, so when a killer comes after them, they wonder if the town of Rosewood will believe them.